Qualitative statistical analysis of senior world wrestling championship 2022 - Belgrade (SRB) - Dokmanac, M. (International Journal of Wrestling Science, 2023)
By applying a new way of analyzing major world championships (Performance Data Analysis - PDA), a completely different approach is obtained in analyzing the wrestling championship. In the first phase of creating PDA, all video matches at the championship were reviewed and data on all segments of wrestling matches were recorded. In the next phase, a qualitative analysis of the wrestling techniques that were shown at the last senior world championship in 2022 in Belgrade (SRB) was made through a prepared platform called Performance Data Analysis - PDA..